Optimizing emotional regulation through digital journaling for improved psychological well-being in generation Z - Batubara, Azizah; Hasanah, Nurul; Hendriko Purba, Gufanta; Triyuda, Rangga (Indonesian Research Journal in Education |IRJE|, 2025)
This research examined the optimization of emotional regulation through digital journaling to enhance psychological well-being in Generation Z. The research employed an experimental method with a non-equivalent control group design. The sample consisted of 30 people in the experimental group and 30 people in the control group. The data collection instrument was the Emotion Regulation Questionnaire (ERQ) scale and the Ryff Psychological Well-being Scale. The treatment employed was digital journaling using the Canva application, and the hypothesis testing method used was the t-test. The research results showed an increase in emotional regulation in the experimental group, which was correlated with the participants’ level of psychological well-being.  There were differences in the levels of emotional regulation and psychological well-being between the experimental and control groups.